Synthesis and performance evaluation of a polymer microsphere based nanosilica as a cementing fluid loss reducer. Issue 1 (22nd December 2017) - Zhang, Jian; Peng, Zhigang; Zou, Changjun; Chen, Dajun; Zhang, Bojian; Jiao, Libin
Abstract : Polymer microspheres (ZJD-220) comprising styrene, butyl acrylate (BA) and methyl methacrylate (MMA) were prepared by soap-free emulsion polymerisation, utilising 2-acrylamido-2-methyl propane sulfonic acid (AMPS) and sodium p-styrene sulfonate (SSS) as anionic copolymer emulsifiers, and used as a novel temperature-resistant fluid loss reducer for oil well cement. The influence of the anionic copolymer emulsifier on the properties of the polymer microspheres was assessed and the fluid loss performance of cement slurries modified by ZJD-220 was evaluated. The ratio and amount of AMPS and SSS were found to have an obvious influence on the characteristics of the polymer microspheres, whose particle size distribution was uniform and monodisperse. The ZJD-220 had excellent thermal resistance and a typical core–shell structure. The fluid losses of freshwater- and salt-based cement slurries (18% sodium chloride) modified with ZJD-220 were controlled within 43 ml and 75 ml, respectively, when the mass fraction of ZJD-220 was 3·0% of the total mass of cement under an ultra-high temperature of 200°C (bottom-hole circulating temperature). Evaluation of the performance of ZJD-220 mixed into different kinds of cement systems with other additives showed that ZJD-220 has good compatibility with different cement slurry systems and additives. Cement slurry with added ZJD-220 showed excellent ability to control filter loss due to the 'adsorption, bridge-building, film-filling and plugging' synergistic reaction of the ZJD-220 filling gaps between cement particles and the filter cake pores.